PWE-207 Predictors of survival following percutaneous transhepatic biliary drainage. (22nd June 2015) - Peplow, C; King, A; Nurhussein, A; Ghandhi, N; Ganeshan, A; Mottershead, M; Wilson, P
Abstract : Introduction: Percutaneous transhepatic cholangiography and biliary drainage (PTC) is an effective therapeutic intervention in the management of benign and malignant biliary tract disease. As predictors of outcome following PTC are not well established, we sought to investigate outcomes after PTC and identify patients most at risk of complications. Method: We performed a retrospective analysis of patients undergoing PTC between January 2012 and January 2014. Results: 78 patients underwent 128 procedures. 85% of procedures were undertaken for malignant disease, of those, 50% were for palliative management only. Overall 30 day mortality was 21.8%. Multivariate analysis showed pre procedure serum albumin and development of acute kidney injury (AKI) post procedure to be significant independent predictors of mortality (p < 0.05). AKI following PTC dramatically reduced median survival (11 days vs 114 days with no AKI, log rank p < 0.05) and was associated with advancing age and higher pre procedure serum creatinine (p < 0.05). Sepsis following PTC occurred in 61% but did not affect overall survival. Conclusion: AKI following PTC is associated with increased mortality and patients at risk can be predicted by age and pre PTC creatinine. Identification of patients at risk, optimisation of renal function pre procedure and careful peri procedural management of fluid balance may help improve outcomes following PTC. Disclosure of interest: None Declared.